Galaxy Zoo CEERS: Bar Fractions Up to z ∼ 4.0 - Tobias Géron; R. J. Smethurst; Hugh Dickinson; L. F. Fortson; Izzy L. Garland; Sandor Kruk; Chris Lintott; Jason Shingirai Makechemu; Kameswara Bharadwaj Mantha; Karen L. Masters; David O’Ryan; Hayley Roberts; et al. (The Astrophysical Journal, 2025)
We study the evolution of the bar fraction in disk galaxies between 0.5 <  z  < 4.0 using multiband colored images from JWST Cosmic Evolution Early Release Science Survey (CEERS). These images were classified by citizen scientists in a new phase of the Galaxy Zoo (GZ) project called GZ CEERS. Citizen scientists were asked whether a strong or weak bar was visible in the host galaxy. After considering multiple corrections for observational biases, we find that the bar fraction decreases with redshift in our volume-limited sample ( n = 398); from $2{5}_{-4}^{+6}$ % at 0.5 < z < 1.0 to ${3}_{-1}^{+6}$ % at 3.0 <  z  < 4.0. However, we argue it is appropriate to interpret these fractions as lower limits. Disentangling real changes in the bar fraction from detection biases remains challenging. Nevertheless, we find a significant number of bars up to z = 2.5. This implies that disks are dynamically cool or baryon dominated, enabling them to host bars. This also suggests that bar-driven secular evolution likely plays an important role at higher redshifts. When we distinguish between strong and weak bars, we find that the weak bar fraction decreases with increasing redshift. In contrast, the strong bar fraction is constant between 0.5 < z < 2.5. This implies that the strong bars found in this work are robust long-lived structures, unless the rate of bar destruction is similar to the rate of bar formation. Finally, our results are consistent with disk instabilities being the dominant mode of bar formation at lower redshifts, while bar formation through interactions and mergers is more common at higher redshifts.